Investigating the relationship between parenting style and dental anxiety in children aged 7 to 12 years in Tehran - Asie Eftekari; Maryam Bakhtiari; Amir Sam Kianimoghadam (Tehran University of Medical Sciences, 2021)
Background and Aims: Studies have shown that dental anxiety may be caused by various factors such as child mood, age, maternal emotional maturity, previous dental anxiety and parenting styles. Therefore, the aim of this study was to investigate the possible relationship between the parenting styles and pediatric dental anxiety and the predictability of this variable through parenting styles. Materials and Methods: The present study was a cross-sectional correlational study. The study population was children aged 7 to 12 years who had referred to the dental clinics of Tehran in 1400. Sampling from one of the clinics was done randomly. A total of 100 questionnaires of modified child dental anxiety scale and parenting style inventory were given to the children and their parents and 95 of them could have been analyzed. The questionnaires were analyzed using SPSS22 software and Pearson correlation and regression tests. Results: The results showed that dental anxiety had a negative and significant relationship with authoritative parenting style (r=-0.286, P<0.01) and a positive and significant relationship with authoritarian parenting style (r=0.342, P<0.01). Authoritarian parenting style can be a predictor of dental anxiety. Conclusion: Knowing the predictors of dental anxiety can help a pediatric dentist analysing who is most prone to dental anxiety. Based on this approach, a relationship based on trust can be established between the dentist and parents to make the necessary recommendations to parents in the office, reduce dental anxiety and improve oral health conditions in children.